Ichthyofauna of the Mata de Itamacaoca, an urban protected area from the upper Munim River basin, Northern Brazilian Cerrado - Oliveira, Elioenai da Silva; Guimarães, Erick Cristofore; Brito, Pâmella Silva de; Vieira, Lucas de Oliveira; Oliveira, Rafael Ferreira de; Campos, Diego Sousa; Katz, Axel Makay; South, Josie; Nunes, Jorge Luiz Silva; Ottoni, Felipe Polivanov (Biota Neotropica, 2020)
Abstract: The Munim River basin is one of the main river drainages of the Hydrological unit Maranhão, but there are few published studies which focus on ichthyological surveys and taxonomic work within this basin. The present study aims to provide a fish species inventory of the Mata da Itamacaoca, one of the few urban protected areas from the upper Munim River basin, comparing the ichthyofauna with other lists by conducted at the upper Munim River basin. A total of 42 collection expeditions were conducted, the sampling was conducted at five collecting sites distributed within the boundaries of Mata de Itamacaoca, upper Munim River basin. Diversity indices were calculated and generalised linear models (GLMs) were employed to assess differences in species richness, diversity and evenness depending on season and location in relation to the reservoir dam wall. In order to visualize fish community differences, non-metric multidimensional scaling (nMDS) and a one-way PERMANOVA was used to understand whether factors of site, season and location to the dam wall had an effect on fish community compositions. A total of six orders, 13 families, and 23 fish species were found, and the order with the highest species richness, considering all reaches, was Characiformes followed by Cichliformes. The most abundant species was Nannostomus beckfordi, while Pimelodella parnahybae and Hoplerythrinus unitaeniatus were the rarer species sampled. There were no alien invasive species collected within the study area. Species richness was significantly higher below the dam wall, but there were no other significant differences in diversity indices with regards to season or location. Fish community composition was significantly different above and below the dam wall and was significantly affected by sampling site. Season did not have an effect on fish community. This study corroborates other studies conducted in the Unidade Hidrológica Maranhão sensu Hubbert and Renno (2006), that the ichthyofaunal composition and taxonomy of species within this region face major data deficits, anthropogenic impacts, this study may be a baseline for comparing similar environments throughout the region.